An invitation to analytic abduction. (December 2021) - Halpin, Michael; Richard, Norann
Abstract: This paper provides an invitation to analytic abduction, an emerging approach to qualitative research. Like deduction and induction, abduction is a mode of inquiry. In a general sense, abduction forwards explanations for novel or surprising observations. In a more practical sense, abduction aims to combine the strengths of both inductive and deductive inquiry by reasoning from concrete data (similar to induction), but using this data to extend, refine, or refute existing theories or propositions (similar to deduction). In this paper, we provide an overview of how and why abduction was developed for qualitative research before demonstrating how to apply analytic abduction to real-world data. Our examples connect data to longstanding and well-researched theories in psychology to highlight the utility of abduction for psychological researchers. We argue that analytic abduction is an ideal resource for qualitative psychologists, as the approach emphasizes qualitative data while leveraging such data to shape theory. This focus on theory provides ample opportunities to use qualitative work to inform concepts central to psychological science, including those that are primarily tied to experimental design, quantitative methods, and deductive reasoning.